Edmodo Based e-Learning Development on Science Lesson in 7th Grade - Totok Suhaeri; Mustaji Mustaji; Suryaman Suryaman (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
This research aims to produce Edmodo-based e-learning that is feasible and effective to improve science learning outcomes. This research uses a modified Borg & Gall (1983) model. Data collection tools are in the form of questionnaire and test. Data analysis technique used is descriptive analysis. The results showed that the average validation score (1) of the media expert was 4.6 (very valid); (2) peers were 4.5 (very valid); (3) the material expert was 4.5 (very valid); (4) user limited test group is 3.8 (valid); (5) implementation group is 4.1 (valid). To test the effectiveness of e-learning and interactive learning media in improving learning outcomes in Natural Science learning for 7th graders. Based on the pretest results, it obtained an average value of 5.80, then on the posttest results showed an average increase to 75.60. Based on the results of research, it can be concluded that Edmodo-based e-learning developed is feasible and effective to be used in Natural Science learning.